2016
DOI: 10.17344/acsi.2016.2911
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Evaluation of 5-Methyl-6-acetyl Substituted Indole and Gramine

Abstract: The synthesis and crystal structures of 1-(5-methyl-1H-indol-6-yl)ethan-1-one (7), C 11 H 11 NO, and 1-{3-[(dimethylamino)methyl]-5-methyl-1H-indol-6-yl}ethan-1-one (8), C 14 H 18 N 2 O, are reported. The synthesis is based on the Diels-Alder cycloaddition of a substituted 2H-pyran-2-one derivative, followed by an acid-catalyzed cyclization and concomitant deprotection (the last two steps were carried out as a one-pot domino process) yielding substituted indole 7, which was further derivatized via Mannich reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…In 2016, compound 27 was prepared using the Diels-Alder cycloaddition reaction, with compound 26 as the dienophile. Then, the substituted indole 28 was obtained via acid-catalyzed cyclization and concomitant deprotection, which further derivatized to the gramine analogue 29 via the Mannich reaction [22]. Scheme 4.…”
Section: Zinc-chloride-catalyzed Reactionmentioning
confidence: 99%
“…In 2016, compound 27 was prepared using the Diels-Alder cycloaddition reaction, with compound 26 as the dienophile. Then, the substituted indole 28 was obtained via acid-catalyzed cyclization and concomitant deprotection, which further derivatized to the gramine analogue 29 via the Mannich reaction [22]. Scheme 4.…”
Section: Zinc-chloride-catalyzed Reactionmentioning
confidence: 99%
“…[27][28][29][30][31] Namely, it was already observed that 2H-pyran-2-ones can act as "double" dienes, reacting in two consecutive Diels-Alder reactions with two distinctive molecules of the dienophiles, yielding bicyclo[2.2.2]octenes. 30 The initial cycloaddition step leads to the formation of CO 2 -bridged oxabicyclo[2.2.2]octenes that in the next step eliminate a molecule of CO 2 (via a retro-hetero-Diels-Alder reaction) providing cyclohexadiene systems that act as new dienes for another molecule of dienophile finally providing the double cycloadducts.…”
Section: Synthesismentioning
confidence: 99%
“…The chlorination of diclofenac (1) (Scheme 1, step 1) was attempted under three conditions, as previously reported in the literature: [10][11][12] (i) reux conditions with an excess of thionyl chloride (SOCl 2 ) for 2 h, 10 resulting in the degradation of diclofenac (1), observed by 1 H-NMR spectra; (ii) reaction with oxalyl chloride [Cl(CO) 2 Cl] in methylene chloride (DCM) at room temperature, 11 that did not yield the acid chloride 2 even at long periods of time (up to 72 h); and (iii) the use of few drops of N,N-dimethylformamide (DMF) as catalyst for the reaction for oxalyl chloride, which turned out to be the optimal conditions with quantitative yields (99%). 12 Regarding to molecular cyclization to render the lactam 1-(2,6-dichlorophenyl)indolin-2-one (3) (Scheme 1, step 2), several procedures have been published on the literature: radical photoredox cyclization, 13,14 acid catalyzed cyclization 15,16 and Mn(III)-based oxidative cyclization methods, 17 as well as 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC)-based carboxyl activation cyclization, 18 among others. Nevertheless, these methods present limitations, including multiple steps, complex catalysis and use of expensive reagents.…”
mentioning
confidence: 99%